Zircon U–Pb and Lu–Hf isotope study of the Neoproterozoic Haizhou Group in the Sulu orogen: Provenance and tectonic implications - Zhou, J.; Wilde, Simon; Liu, F.; Han, J. (Elsevier BV, 2012)
The Neoproterozoic Haizhou Group crops out sporadically in the Sulu orogen in east-central China. It is divided into the Jinping and Yuntai formations and consists of quartzite, quartz schist, marble and graphite- and apatite bearing sequences. Major and trace element data for quartz schist from the two formations indicate that these rocks have a greywacke protolith and have been deposited during strong tectonic activity. LA-ICPMSU–Pb dating of detrital zircon yields ages of 635 to 1074Ma for three samples from the Jinping Formation and 611 to 943 Ma for two samples from the Yuntai Formation. More than 78% of the detrital zircons from the two formations have U–Pb ages grouped between 700 and 890 Ma, with two clusters peaking at 758 Ma and 828 Ma, respectively. This indicates that their provenance is magmatic rocks of Neoproterozoic age that have a tectonic affinity to the South China Block (SCB).A few older zircon populations with peak U–Pb ages at 943 and 1074 Ma are also present. A younger population shows peaks at 661 and 611 Ma. This suggests that deposition of the Haizhou Groupwas later than ~611 Ma rather than during the Mesoproterozoic as previously thought. Zircon Lu–Hf isotope data collected from the same U–Pb sites show negative εHf(t) values of-22.8 to-7.4 and Hf model ages of 2341 to 3100Ma. This indicates that the Neoproterozoic magmatic rockswere derived from reworking of ancient Paleoproterozoic to Archean crust. The results support the contention that the Haizhou Group is similar to the Wulian Group at the northwestern edge of the Sulu orogen, both having a SCB affinity, but that the Penglai Group does not belong to the SCB because of the absence of Neoproterozoic ages. This lends support to the conclusion that the Triassic suture between the North China and South China blocks is located along the Baichihe–Yantai Fault, which lies north of the Wulian Complex and south of the Jiaobei Terrane; thus the Wulian–Yantai Fault is not the suture zone as is traditionally proposed.